Microspheres: A Review - Khedkar S. , Anuradha; Dr. Nishan N. Bobade,; Dr. Vikrant P. Wankhade,; Dr. Sandeep C. Atram,; Dr. Shrikant D. Pande,; Deshmukh P. Nishant,; Patil A. Mahendra, (Asian Journal of Pharmaceutical Research and Development, 2025)
Multiparticulate drug delivery systems called microspheres are made to deliver drugs for extended periods of time or under controlled conditions, enhancing stability and bioavailability while delivering the drug to a specific location at a predefined rate. They are composed of natural, semi-synthetic, and synthetic polymers, as well as polymeric waxy or other protective materials. Microspheres are free-flowing powders made of proteins or synthetic polymers with particle sizes between 1 and 1000 μm. The different kinds of microspheres, their preparation techniques, and their uses are highlighted in this review. There are many different kinds of microspheres, including bio adhesive, magnetic, floating, radioactive, polymeric, biodegradable, and synthetic. They are made using techniques like spray drying, solvent evaporation, single and double emulsion, phase separation coacervation,Spray drying and spray congealing, Solvent extraction. Microspheres have wide range of applications because of controlled and sustained release.